Taxpayer compliance factor related to technology: the influence of e-registration, e-spt, e-filling, and e-billing usage - Moh. Fitrah Ramadhan; Janiman Janiman; Arinal Muna (RTTM, 2023)
In 2019 the level of taxpayer compliance was only 29% of the total number of taxpayers registered at KPP Pratama Cirebon Satu; then in 2020, there was a decrease of around 6% to 23% of the total WPOP, then in 2021, it only increased 1% to 24% of the total number of taxpayers. Registered WPOP. Based on this, this research is here to see how Taxpayer Compliance in Cirebon is based on E-Registration, E-SPT, E-Filling, & E-Billing. This research method uses the verification method. This type of research is basic research or basic research. The questionnaires that were sent out to individual taxpayers who were registered with the Cirebon Satu Tax Service Office were the source of the primary data that was used in this research. The formula for convenience sampling was used to select the sample, which consisted of a total of 100 participants from the pool. Statistical analysis was carried out in this study using multiple linear regression analysis using IBM SPSS 25 software for windows. The results of this study indicate that E-SPT affects taxpayer compliance in the city of Cirebon. Meanwhile, E-Registration, E-Filling, and E-Billing do not affect Taxpayer Compliance in Cirebon, Indonesia. The contribution of this research can increase recommendations for the government, especially in increasing taxpayer reporting by increasing certainty of validation in tax payments